CHARACTERISTICS OF TRAFFIC ACCIDENTS ON 4/2D ROAD TYPES ON THE SURABAYA - MOJOKERTO TOLL ROAD ( CASE STUDY: WARUGUNG - PENOMPO TOLL ROAD SECTION) - Laksono, Achmad Ipung Dwi; Moetriono, Hary (Fakultas Teknik Universitas Tanjungpura, 2023)
In developing road infrastructure, keeping pace with the transportation sector and the rapidly growing economy is vital. Inadequate road infrastructure conditions will cause problems on the road, namely traffic accidents and congestion, which results in a lack of driver comfort. PT Jasa Marga can undoubtedly find out the leading cause of the accident. This study aimed to determine the characteristics of traffic accidents on the 4/2d road type, precisely on the Surabaya - Mojokerto toll road on the Warugunung - Penompo toll road. The Surabaya